Caffeine and creatine use in sport - Tarnopolsky, M. A. (Annals of Nutrition and Metabolism, 2010)
Caffeine and creatine are 2 of the most widely available and used compounds in sport. Although the use of either is not considered a doping infraction, the evidence does suggest ergogenic potential in certain sports. The purpose of this paper is to review the pharmacology and potential mechanism(s) of action of caffeine and creatine as they pertain to possible use as an ergogenic aid in sport. Methods: Previous review articles on caffeine and creatine use in sport were screened for relevant information and references, and studies for review and recent articles (2007 onwards) were obtained and reviewed using a PUBMED search with the terms `caffeine AND exercise`, `creatine and creatine monohydrate AND exercise`, and appropriate linked articles were evaluated. Results: Caffeine taken before (3-6 mg/kg) or during (1-2 mg/kg) endurance exercise enhances performance, through central nervous system and direct muscle effects. Creatine monohydrate supplementation at higher (approx. 20 g/day × 3-5 days) or lower (approx. 5 g/day × 30 days) doses increases skeletal muscle total and phosphocreatine by 10-20%. Creatine supplementation appears to minimally but significantly enhance high-intensity sport performance and the mass and possibly strength gains made during resistance exercise training over the first few months. Conclusions: Although caffeine and creatine appear to be ergogenic aids, they do so in a sport-specific context and there is no rationale for their simultaneous use in sport. Higher doses of caffeine can be toxic and appear to be ergolytic. There is no rationale for creatine doses in excess of the recommendations, and some athletes can get stomach upset, especially at higher creatine doses